Cinnamic Acid Increased the Incidence of Fusarium Wilt by Increasing the Pathogenicity of Fusarium oxysporum and Reducing the Physiological and Biochemical Resistance of Faba Bean, Which Was Alleviated by Intercropping With Wheat - Guo, Yuting; Lv, J.; Zhao, Q.; Dong, Yan; Dong, K. (Frontiers in Plant Science, 2020)
Background Continuous cropping has resulted in the accumulation of self-toxic substances in faba beans which has restricted their global production. Intercropping is widely used to alleviate these problems. Aims To explore the role of cinnamic acid stress in faba bean physiology and disease resistance, and the potential mitigating effects of intercropping the faba bean with wheat. Methods Faba bean seedlings were grown with or without wheat in both field and hydroponic conditions in the presence of different cinnamic acid concentrations and Fusarium oxysporum (FOF), the occurrence of. Fusarium-mediated wilt and oxidative stress, as well as plant growth indices and the anti-pathogen defense system were analyzed. Results Cinnamic acid significantly increased Fusarium pathogenicity, inhibited the activity of defense enzymes and reduced the ability of plants to resist pathogens, indicating the importance of cinnamic acid in the promotion of Fusarium wilt resulting in reduced seedling growth. Intercropping with wheat improved plant resistance by alleviating cinnamic acid-induced stress, which promoted crop growth and decreased the incidence and disease index of Fusarium wilt. Conclusion Cinnamic acid promotes Fusarium wilt by stimulating pathogen enzyme production and destroying the defense capability of faba bean roots. Intercropping reduces Fusarium wilt by alleviating the damage caused by cinnamic acid to the defense system of the faba bean root system.